Actions of Prolactin in the Brain: From Physiological Adaptations to Stress and Neurogenesis to Psychopathology - Torner, Luz (Frontiers in Endocrinology, 2016)
Prolactin is one of the most versatile hormones known. It is considered an adaptive hormone due to the key roles it plays in the modulation of the stress response and during pregnancy and lactation. Within the brain, prolactin acts as a neuropeptide to promote physiological responses related to reproduction, stress adaptation, neurogenesis, and neuroprotection. The action of prolactin on the nervous system contributes to the wide array of changes that occur in the female brain during pregnancy and result in the attenuation of the hypothalamic pituitary adrenal axis. Together, all these changes promote behavioral and physiological adaptations of the new mother to enable reproductive success. Brain adaptations driven by prolactin are also important for the regulation of maternal emotionality and wellbeing Prolactin also affects the male brain during the stress response but its effects have been less studied. Prolactin regulates neurogenesis both in the subventricular zone and in the hippocampus. Therefore, alterations in the prolactin system due to stress, or exposure to substances that reduce neurogenesis or other conditions, could contribute to maladaptive responses and pathological behavioral outcomes. Here we review the prolactin system and the role it plays in the modulation of stress response and emotion regulation. We discuss the effects of prolactin on neurogenesis and neuroprotection, the putative neuronal mechanisms underlying these effects, and their contribution to the onset of psychopathological states like depression.